1987
DOI: 10.1590/s0071-12761987000200034
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos da biologia de Trichogramma demoraesi Nagaraja, 1983 e contribuições ao manejo de criações massais deste parasitóide em ovos de Anagasta kuehniella (Zeller, 1879)

Abstract: Resultados de ensaios de laboratório evidenciaram um efeito negativo da idade adulta do Trichogramma demoraesi a partir dos seis dias de vida, sobre o parasitismo de ovos de Anagasta kuehniellae a duração da fase imatura do parasitóide, segundo uma equação de regressão polinomial de terceira ordem. As maiores taxas de parasitismo e duração da fase imatura, para insetos alimentados ou não com solução de mel a 50%, foram propiciadas pelos adultos com 4-6 dias de idade, sendo nulo o parasitismo por insetos com de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Similar results for T. minutum showed that longevity decreased without a defined sequence from 29.2 to 20.8 days for parasitoids receiving host eggs one to 16 days after emergence (Leatemia et al, 1995a). Santa-Cecília et al (1987) reported that T. demoraesi had similar longevity patterns up to the 10 th day without a host, after which a sharp decline occurred regardless of the feeding regime. An important finding in these studies is the existence of a threshold point after which a significant parasitoid longevity decrease occurs.…”
Section: Longevitysupporting
confidence: 62%
See 1 more Smart Citation
“…Similar results for T. minutum showed that longevity decreased without a defined sequence from 29.2 to 20.8 days for parasitoids receiving host eggs one to 16 days after emergence (Leatemia et al, 1995a). Santa-Cecília et al (1987) reported that T. demoraesi had similar longevity patterns up to the 10 th day without a host, after which a sharp decline occurred regardless of the feeding regime. An important finding in these studies is the existence of a threshold point after which a significant parasitoid longevity decrease occurs.…”
Section: Longevitysupporting
confidence: 62%
“…This parasitoid should, therefore, be released in places adequate for host finding because, besides expending energy on parasitizing, it also uses energy searching for hosts. Santa-Cecília et al (1987) found no differences in longevity of T. demoraesi adults with (11.59 days) or without (11.38 days) supplemental feeding, while Leatemia et al (1995b) reported longevity of 26.4 and 3.5 days for adults of T. minutum, with or without honey, respectively. Cônsoli & Parra (1994) showed longevity of 3.77 days for T. galloi fed with honey, in eggs of D. saccharalis.…”
Section: Longevitymentioning
confidence: 79%
“…However, not all species or strains of the genus Trichogramma have longer longevity when fed which shows the importance of studies addressing this subject. T. demoraesi females had similar longevity of 11 days whether fed or not fed (Santa-Cecília et al, 1987). Mating also influenced the adult longevity, mainly for T. pretiosum.…”
Section: Resultsmentioning
confidence: 93%
“…Adult feeding also increased the parasitism by T. perkinsi and T. australicum (Somchoudhury and Dutt, 1988). However, this characteristic could vary from species to species because fed and unfed T. demoraesi females showed similar parasitism rate (Santa-Cecília et al, 1987). Other factors besides adult feeding such as strains, parasitoid species, host quality and temperature can affect the parasitism of Trichogramma spp (Lopes, 1988;Maceda et al, 2003;Pinto and Tavares, 1992;Pratissoli et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Berti and Marcano (1993) reported low longevity for T. pretiosum in eggs of S. cerealella (5.9 days). However, species such as T. minutum (Leatemia et al ., 1995) and Trichogramma demoraesi Nagaraja, 1983 (Hymenoptera: Trichogrammatidae) presented longer longevity, 26.4 and 11.6 days, respectively (Santa-Cecília et al ., 1987), than T. pretiosum. Longevity of egg parasitoids can be influenced by species and/or strain of these natural enemies and also by rearing methodology and by their host.…”
mentioning
confidence: 99%